Novel defenses of Protopulvinaria pyriformis (Hemiptera: Coccidea) against its major parasitoid Metaphycus helvolus (Hymenoptera: Encyrtidae): Implications for biological control of soft scales - Tena, Alejandro; Beltrá, Aleixandre; Soto, Antonia (2017)
Protopulvinaria pyriformis (Cockerell) (Hemiptera: Coccidae), a scale native to South America, is a major pest of laurel, Laurus nobilis L., and a potential pest of other ornamental plants in urban green areas. We evaluated the potential of Metaphycus helvolus (Compere) (Hymenoptera: Encyrtidae), its major parasitoid, as a biological control agent against P. pyriformis. This parasitoid was imported from South Africa to control soft scales in Europe more than 20 years ago. Three factors limited its efficacy: (i) the scale frequently thwart parasitoid attack by removing its stylet and wiggling, a unique defense in soft scales, (ii) scale honeydew extended M. helvolus lifespan little more than water, and (iii) P. pyriformis did not encapsulate Metaphycus spp. eggs but immature parasitoids died during their prepupal stage, which may have been caused by laurel plant secondary compounds from laurel. This parasitoid mortality had not been previously reported in immature parasitoids of genus Metaphycus. These three novel aspects should be considered when choosing a suitable parasitoid in future soft scale biological control programs. (C) 2012 Elsevier Inc. All rights reserved.